PENGARUH FAKTOR-FAKTOR STRESS KERJA TERHADAP KINERJA PADA PERAWAT RUMAH SAKIT DI KABUPATEN TUBAN - Teman Koesmono; Agnes Arshinta Dewi (EKUITAS (Jurnal Ekonomi dan Keuangan), 2007)
The purpose of this research is to find out how far the stress in the work place that suffered by nurses can effect their working performance. The researcher is interested in observing the effect of the stress in the work place on nurses’ working performance in Tuban Region because the nurses in doing their jobs are suspected to have heavy working stress. That’s because a nurse is faced to a specific job and put his/her service as a priority for the sick patients who is suffering from their deseases. The effect of patients’ behavior and even their families makes a nurse working extra hard in order to keep out the negative judgement against the hospital where they work. The result of this research found that working stress attributes which are: Administrative Policies and Strategies, Organizational Structure and Designs, Organizational Process and Working Conditions significantly effect a nurses working performance in the hospital in Tuban Region. This is important to know because a nurse plays an important role as a paramedic in giving his/her contribution to the patients regarding to heal their deseases.